Determination of polymer additive residues that migrate from coffee capsules by means of stir bar sorptive extraction-gas chromatography-mass spectrometry and PARAFAC decomposition. (June 2021) - Valverde-Som, L.; Reguera, C.; Herrero, A.; Sarabia, L.A.; Ortiz, M.C.
Highlights: Method for ultra-trace determination of plastic additive residues is developed. PARAFAC enables the unequivocal identification in the presence of coeluting compounds. Traces of BHT, BP and DiBP in Milli-Q water vary depending on the day of collection. BHT and BP migrate from coffee capsules but far below their specific migration limits. DiBP migrates from the coffee capsules are found in coffee around its legal limit. Abstract: This paper reports on the difficulties encountered when developing an analytical method for ultra-trace determination, in a complex matrix, of plastic additive residues which are ubiquitous in the laboratory. The simultaneous qualitative and quantitative determination of an antioxidant (2, 6-di-tert-butyl-4-methyl-phenol, BHT), an UV stabilizer (benzophenone, BP), and a plasticizer (diisobutyl phthalate, DiBP), released from plastic capsules is carried out in coffee by means of GC–MS and parallel factor analysis decomposition. Stir bar sorptive extraction is used to extract and concentrate the analytes. Coffee samples are prepared with Milli-Q water, which contains residues of the target compounds, which can be significant for ultra-trace analysis and should be subtracted. In addition, matrix effect exits in coffee, so standard addition method is used. The residue concentrations released from the coffee capsules into the solid coffee are around 3, 1, and 12 μg kg −1 of BHT, BP and DiBP, respectively.